ANALISIS GAME IMMERSION BERBASIS AUGMENTED REALITY “ANGRY BIRD AR: ISLE OF PIGS” TERHADAP PENGALAMAN PEMAIN - Dopades, Mario; Sumarlin, Rully; Rahadianto, Irfan Dwi (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2024)
Rapid technological developments in the modern era produce technological products such as Augmented Reality (AR). Currently, AR has been utilized as an information technology that supports the productivity of various fields such as education, medical, military, industry, and entertainment. One of the uses of AR in the entertainment field can be seen in the emergence of AR-based games in the game mechanism. AR-based games have started to emerge since the high public interest in the Pokemon GO game in 2016; until now, games have appeared as a result of the transformation that was originally a video game-based game into an AR-based game such as Angry Bird AR. It is very compelling to learn more about how AR-based games' user experience can affect game immersion as an important aspect of game development. The research method employed was a quantitative method using the game experience questionnaire (GEQ) as a measuring tool to assess the influence of game immersion variables on user experience in the Angry Birds AR: Isle of Pigs game. This study found that game immersion has a positive impact on player user experience, but it is essential to consider flow aspects, especially in building the game world. Keywords: Augmented Reality, Game, Game Immersion, User Experience.